2004
DOI: 10.1211/0022357023718
|View full text |Cite
|
Sign up to set email alerts
|

Consumer attitudes towards community pharmacy services in Saudi Arabia

Abstract: Objective The purpose of this study was to determine consumer attitudes towards community pharmacy and their preferences for the introduction of new services. Methods A self‐completion questionnaire was developed and 1,144 consumers in 55 community pharmacies were invited to complete it. The questionnaire covered consumers' choice of pharmacy; their perceptions of, and actual interactions with, community pharmacists; advice from pharmacists about general health and prescribed medicines; and privacy in the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 12 publications
11
63
0
Order By: Relevance
“…The survey instrument was developed based on a study conducted in Saudi Arabia by Bawazir [6]. The questionnaire was pilot tested using 10 randomly chosen consumers.…”
Section: Methodsmentioning
confidence: 99%
“…The survey instrument was developed based on a study conducted in Saudi Arabia by Bawazir [6]. The questionnaire was pilot tested using 10 randomly chosen consumers.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the greatest experience and highest level of satisfaction was reported by patients when 'receiving medication with care and full attention ' (n=3.26) and 'the way the pharmacist answers patients' questions, when asking (n=3.23), whilst 'allocating time to answer patients' questions' and 'allocating time to prepare medications' were associated with the lowest level of satisfaction by participants. However, in a study of 1,144 consumers of 55 community pharmacies in Saudi Arabia, it was found that 44.8% of participants felt that pharmacists in Saudi Arabia had given them enough time to discuss their issues completely and had listened to their health-related issues (Bawazir 2004). Furthermore, in another cross-sectional descriptive study, conducted in Iran by Mehralian et al, (Mehralian et al, 2014) amongst 800 patients of 200 community pharmacies, it was reported that the highest satisfaction level was mainly related to two domains, 'observe courtesy and respect' and 'reliability of pharmacists' comments', whereas satisfaction with 'allocation of sufficient time to respond to clients' questions' was reported as high or very highly satisfactory by 37.4 % of the participants.…”
Section: Quality Of Communicationmentioning
confidence: 99%
“…It is worth mentioning that only a few studies have been conducted in nearby Arab countries to evaluate patients' satisfaction with the provided pharmacy services; these studies took place in Saudi Arabia (Bawazir 2004), Qatar (El Hajj 2011, and Palestine (Khdour and Hallak 2012). In contrast, in the UAE, this area remains unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of these publications reached a conclusion that community pharmacy is not a well-established health profession. Despite this, the general public in the Arab world reported positive perception and attitude toward community pharmacy profession and demanded more roles for community pharmacists in the health system [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%